2012
DOI: 10.1107/s0907444911052085
|View full text |Cite
|
Sign up to set email alerts
|

Global radiation damage at 300 and 260 K with dose rates approaching 1 MGy s−1

Abstract: Global radiation damage to 19 thaumatin crystals has been measured using dose rates from 3 to 680 kGy s⁻¹. At room temperature damage per unit dose appears to be roughly independent of dose rate, suggesting that the timescales for important damage processes are less than ∼1 s. However, at T = 260 K approximately half of the global damage manifested at dose rates of ∼10 kGy s⁻¹ can be outrun by collecting data at 680 kGy s⁻¹. Appreciable sample-to-sample variability in global radiation sensitivity at fixed dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
34
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 48 publications
5
34
1
Order By: Relevance
“…Thus, the D 1/2 value reflecting global radiation damage in RT SSX is only marginally dependent on dose rate. Earlier studies have reported the absence of a RT dose rate effect, based on data collected at rates between 3 and 680 kGy/s(27), and that D 1/2 increases by a factor of 1.5 to 2 at 33 MGy/s relative to data collected at dose rates of less than 100 kGy/s(23). Regardless, similar D 1/2 values for global radiation damage at RT were reported in the original…”
supporting
confidence: 63%
See 1 more Smart Citation
“…Thus, the D 1/2 value reflecting global radiation damage in RT SSX is only marginally dependent on dose rate. Earlier studies have reported the absence of a RT dose rate effect, based on data collected at rates between 3 and 680 kGy/s(27), and that D 1/2 increases by a factor of 1.5 to 2 at 33 MGy/s relative to data collected at dose rates of less than 100 kGy/s(23). Regardless, similar D 1/2 values for global radiation damage at RT were reported in the original…”
supporting
confidence: 63%
“…Recently, however, it has been shown that the nonexponential intensity decay at RT could be explained by the nonuniform irradiation resulting from exposure to a Gaussian profile X-ray beam and the resulting "hole burning" effect (23). In contrast to cryocrystallography, where no dose rate effect for global radiation damage has been found (24,25), there is evidence that global radiation damage at RT decreases when collecting data at higher dose rates (23,(26)(27)(28).…”
mentioning
confidence: 99%
“…The obvious exception to this relation is the influence of temperature, where it is well-established that at lower temperatures a crystal can withstand a greater dose before it reaches the same extent of global damage, due to the retardation or even prevention of secondary radiation effects [47,48]. Other reported exceptions that influence a dose-damage scaling law by a small factor (<3) are the beam spot size (in the range where it becomes smaller than the electron mean free path (about 4 m)) [49] and the dose rate in the range of 200-300 K [50][51][52] (at lower temperature the effect is in general reported to be absent [37]). …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, RT studies using both rotating-anode and synchrotron sources have shown a significant variation in crystal lifetime as a function of the rate at which dose is deposited in the crystal (Blake & Phillips, 1962;Southworth-Davies et al, 2008;Rajendran et al, 2011;Warkentin et al, 2011). A dose-rate effect has also recently been observed at 260 K (Warkentin et al, 2012). These observations are consistent with datacollection times being comparable with the timescales of X-ray-induced chemical reactions and raise the exciting possibility of significantly increasing the amount of data that can be collected from a crystal by changing the way in which data are collected.…”
Section: Introductionmentioning
confidence: 99%